2014
DOI: 10.1021/nn500685h
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronate–Gold Nanoparticle/Tocilizumab Complex for the Treatment of Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory immune disease causing the inflammation of synovial membrane and the articular cartilage destruction. In this work, hyaluronate-gold nanoparticle/Tocilizumab (HA-AuNP/TCZ) complex was prepared for the treatment of RA. AuNP was used as a drug carrier with antiangiogenic effect. TCZ is a humanized monoclonal antibody against the interleukin-6 (IL-6) receptor and used as an immunosuppressive drug by interfering IL-6 in the pathogenesis of RA. HA is known to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(123 citation statements)
references
References 33 publications
3
117
0
3
Order By: Relevance
“…Tocilizumab-loaded hyaluronate-gold nanoparticles targeted with a monoclonal antibody against IL-6 have also been tested in CIA mice. 95 In another study, the delivery of MTX was achieved using theranostic gold half-shell NPs targeted with RGD peptides. 96 It was revealed that a much smaller dose of these NPs showed greater therapeutic effects than that of a conventional treatment with MTX solution in CIA mice.…”
Section: Targeted Np Approach In Ramentioning
confidence: 99%
“…Tocilizumab-loaded hyaluronate-gold nanoparticles targeted with a monoclonal antibody against IL-6 have also been tested in CIA mice. 95 In another study, the delivery of MTX was achieved using theranostic gold half-shell NPs targeted with RGD peptides. 96 It was revealed that a much smaller dose of these NPs showed greater therapeutic effects than that of a conventional treatment with MTX solution in CIA mice.…”
Section: Targeted Np Approach In Ramentioning
confidence: 99%
“…Among these, the hypoxia-vascular endothelial growth factors (VEGF)-angiopoietin system plays a central role [5]. In addition, several adhesion molecules including α v β 3 integrins, E-selectin, vascular cell adhesion molecule-1 (VCAM-1), and intercellular cell adhesion molecule-1 are over-expressed on the surface of endothelial cells [5,[7][8][9][10]. Macrophages, abundant in the inflamed synovial membrane, possess broad proinflammatory potential and contribute considerably to inflammation and joint destruction.…”
Section: How To Design An Active Targeting Nanomedicine For Ra Treatmentmentioning
confidence: 99%
“…Currently, gold nanoparticles (AuNPs) were exploited as therapeutic treatment for rheumatic diseases attributed to their anti-inflammatory and antiangiogenic actions [17]. Inspired by this property, Lee et al [10] prepared hyaluronate-AuNPs/Tocilizumab (HA-AuNP/tocilizumab (TCZ)) complex with dual targeting effects. AuNP could actively bind to VEGF and TCZ, the first therapeutic antibody against IL-6 signaling, could target to IL-6R.…”
Section: Applications Of Active Targeting Nanomedicinesmentioning
confidence: 99%
“…The work by Lee et al is among few studies that developed a targeted delivery system for a monoclonal antibody. A stable hyaluronate/gold nanoparticle/tocilizumab (HA-AuNP/TCZ) complex was synthesized for the successful treatment of RA in mouse model (73).…”
Section: Delivery Challenges In Biological Therapymentioning
confidence: 99%